Women and Community Services in Islamic History - Alotaibi, Hessa (Journal of Al-Tamaddun, 2021)
The concept of women rights, freedoms, and their role in public sphere are few important areas which have been in news in the past few decades. There is no doubt that women were deprived of their rights such as right to vote, freedom to mobility etc. in Muslim communities in the past few centuries. However, not much later, the fight for women rights and freedoms are being observed among the various Muslim communities. Another aspect among the Islamic communities is related to social service. The foundation of Islam religion was based on the principles of social justice, equality and service to mankind. However, both these concepts including women role and social services in Islam have been influenced by various factors since the founding of Islam religion. Therefore, it would be an interesting area of research to investigate evolution and changes relates to these two areas through the Islamic ages in order to analyse if factors of influence and whether or not these changes are relevant in the current times. Accordingly, the purpose of this paper is to review the role of women and community services through Islamic ages, and analyse its implications in the current scenario. A narrative review approach is adopted in this study in order to reflect the developments from the history. Findings from the review indicated that the women in Islamic ages enjoyed equal rights and status in society in contrast to the women in the modern world. However, social services continued to be a part of the Islamic principles since its emergence in the 6th century. It can be concluded that there is a need to create awareness among the Muslim elites (who base discrimination in the context of religion, culture, and traditions) regarding the equality rights for women and their increased participation in social, economic, and cultural fields in the society.